Enterprise risk and opportunity management : concepts and step-by-step examples for pioneering scientific and technical organizations - Benjamin, Allan S. (Wiley finance series., 2017)
Risk management strategy for the pioneering technological sector Enterprise Risk and Opportunity Management provides much-needed guidance tailored specifically to the technological sector. While most enterprise risk management guides are written for traditional businesses and finance firms, this book translates effective enterprise risk and opportunity management (EROM) principles into strategies and practices that work for government, nonprofit, and for-profit organizations in the technological space. Originally designed for noncommercial pioneering enterprises like NASA, an entire chapter is now devoted toward applying the methods to profit-making technological enterprises. A 40-year veteran of the tech sector, Dr. Allan Benjamin outlines risk management strategies for organizations in which the advancement and integration of science and technology within complex systems is necessary for accomplishment of the mission. - Resumé vydavatel